The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1954
DOI: 10.1139/m55-002
|View full text |Cite
|
Sign up to set email alerts
|

THE SUCCINOXIDASE SYSTEM INASPERGILLUS NIGER

Abstract: The succinoxidase system of Aspergillzrs niger differs from that of avian and mammalian tissues in its greater lability during preparation and storage but is similar in its sensitivity to malonate, cyanide, azide, and B.A.L., its association with cell particles, and its single pH optimum a t pH 7.3. T h e system is not inhibited by arsenite in concentrations up to 0.01 M. MethodsAspergillus niger, N.R.C. 233, was grown in 200 ml. lots of a medium containing 3% malt extract, 0.5Yo yeast extract, and ly0 glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1959
1959
1969
1969

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 12 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…It was essentially that used by Martin (1954) and consisted of 1 yo glucose, 8% malt extract, and 0.5% yeast extract dispensed in 100 ml. volumes in 500 ml.…”
Section: Cultures On Jluid Media Glucose Malt-extract Yeast Medium ( mentioning
confidence: 99%
“…It was essentially that used by Martin (1954) and consisted of 1 yo glucose, 8% malt extract, and 0.5% yeast extract dispensed in 100 ml. volumes in 500 ml.…”
Section: Cultures On Jluid Media Glucose Malt-extract Yeast Medium ( mentioning
confidence: 99%
“…It has been shown that the TCA cycle is operative during the growth of cultures of A. niger (Ramakrishnan, 1954;Ramakrishnan and Martin, 1954;Yeoman, i960). Martin (1954) detected a conventional succinoxidase system in this fungus. The conclusion that such a system is operating in the cellular oxidation of sugars and other normal metabolites in this fungus was strengthened by the detection in Experiments C and D of labelled cyclic acids after feeding mycelia with radioactive malonate.…”
Section: Tiigermentioning
confidence: 86%